(untitled) (Quinto Sol, 2016)
Since the late 18th century, the countryside of Buenos Aires had received considerable waves of migrants from other provinces though they were progressively superseded by those that originated in Europe. Even if there exist studies based on the general results of the first national census, rarely have the handwritten records been used to examine a given population. We therefore propose to analyze in this article the population that inhabited the countryside of Buenos Aires during the first phase of massive immigration to the area. By making use of a perspective that compares three villages: San Antonio de Areco in the northern zone, Mercedes in the center, and San Vicente in the south. We will pay particular attention to the composition of the population, its origins, the productive activities that its inhabitants carried out and the process of urbanization. The geographical location of the foreigners in the rural villages will also be analyzed, as well as the occupations they preferred to do and how their professional activities were eventually diversified based on respective nationalities.